Across the nightingale floor - Hearn, Lian. (New York : Riverhead Books, 2002)
"In his black-walled fortress at Inuyama, the warlord Iida Sadamu surveys his famous nightingale floor. Constructed with exquisite skill, it sings at the tread of each human foot. No assassin can cross it unheard." "The youth Takeo has been brought up in a remote mountain village among the Hidden, a reclusive and spiritual people who have taught him only the ways of peace. But unbeknownst to him, his father was a celebrated assassin and a member of the Tribe, an ancient network of families with extraordinary, preternatural skills. When Takeo's village is pillaged, he is rescued and adopted by the mysterious Lord Otori Shigeru. Under the tutelage of Shigeru, he learns that he too possesses the skills of the Tribe, and with this knowledge he embarks on a journey that will lead him across the nightingale floor and to his destiny within the walls of lnuyama.".
"Overcome by the intensity of first love and conflicted by split loyalties and his own divided nature, Takeo realizes that he must make his own way on this journey of revenge and treachery, honor and loyalty, betrayal and love."--BOOK JACKET.
Keywords: Teenage boys -- Fiction; Orphans -- Fiction; Japan -- Fiction; Historical fiction; Adventure fiction